Avaliação de um sistema de informação na formação da remuneração de serviços em setor de energia elétrica - Porto, Daniel Sperb (Universidade do Vale do Rio dos Sinos, 2013)
The present study corresponds to the evaluation of an information system in the formation of pay services in the electricity sector. Such remuneration is consistent with the measurement and management of operational costs in order to generate greater rationality of compensation process outsourcing services company in the power sector. The issue problem converges towards managing and measuring the compensation of outsourcers in activities of electric distribution networks. This evaluation is based on a Decision Support System (DSS) to simulate scenarios compensation activities in eletric distribution grid. The methodology employed was the design research (DR), and the results found with the research show that the system built reflects the practical realization of the cost of construction crews grids, realizing even as the particularities treatment activities through to the composition adequate remuneration.
Keywords: Custos; Design research; Distribuição de energia elétrica; Sistema de apoio à decisão; Terceirização; Decision support system; Outsourcing; Costs; Power distribution; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis